Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1073/pnas.84.3.784
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of point mutations in the period gene that stop or speed up biological clocks in Drosophila melanogaster.

Abstract: The pero1 and the pers mutations in Drosophila melanogaster, which seem to eliminate or speed up, respectively, the clocks underlying biological rhythmicity, were mapped to single nucleotides. Chimeric DNA fragments consisting of well-defined wild-type plus mutant DNA subsegments were constructed, introduced into flies by germ-line transformation, and assayed for biological activity. These experiments localized both perol and pers to a 1.7-kilobase DNA fragment that is mostly coding DNA. Sequencing of this sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 26 publications
6
76
0
Order By: Relevance
“…1A). This region includes the per short domain and part of the CLK/ CYC inhibition domain (CCID) (Yu et al 1987;Chang and Reppert 2003). It also contains a number of phosphorylation sites that are critical for controlling clock speed, such as T583, S585, S589, and S596 (Chiu et al 2011).…”
Section: Codon Optimization In the Central Part Of Dper Also Results mentioning
confidence: 99%
“…1A). This region includes the per short domain and part of the CLK/ CYC inhibition domain (CCID) (Yu et al 1987;Chang and Reppert 2003). It also contains a number of phosphorylation sites that are critical for controlling clock speed, such as T583, S585, S589, and S596 (Chiu et al 2011).…”
Section: Codon Optimization In the Central Part Of Dper Also Results mentioning
confidence: 99%
“…The mutant circadian phenotypes observed in per5, and per° flies are due to changes in the per gene's proteoglycan-like gene product Jackson et a!., 1986;Yu et a!., 1987 andBaylies eta!., 1987). The mutant proteoglycans may alter the pattern of intercellular coupling between cells by affecting gap junctional communication (Spray eta!., 1987 andBargiello eta!., 1987) Gap junctions appear to be important during development, because disturbing them can impaii pattern formation (Warner, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are mutations at the per (period) locus. Molecular analysis ofper has shown that deletion of the gene results in arrhythmicity, while a variety of long-and shortperiod rhythms can be produced by amino acid substitutions in the per protein or by changing the level of per expression (8)(9)(10)(11)(12). per is expressed in many cell types throughout development (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%